Concordance between quantitative and semi-quantitative analysis of Tc-99m-pyrophosphate scintigraphy for the diagnosis of transthyretin cardiac amyloidosis in patients with HFpEF. (14th October 2021) - Murat, S; Yalvac, H.E; Mert, G.O; Sivrikoz, I.A; Cavusoglu, Y
Abstract: Background: Transthyretin (TTR) cardiac amyloidosis (CA) is an underdiagnosed cause of heart failure with preserved ejection fraction (HFpEF). Cardiac scintigraphy with 99mTechnetium-pyrophosphate (99mTc-PYP) is referred as a simple, non-invasive and reliable method in the diagnosis of TTR-CA. American Society of Nuclear Cardiology Practice Points recommends two interpretative approaches: the quantitative heart-to-contralateral lung ratio (H/CL) at 1 hour or the semi-quantitative visual assessment at 3 hours after radiotracer injection. Purpose: In this study, we evaluated the concordance between semi-quantitative and quantitative approaches in the diagnosis of TTR CA in patients with HFpEF. Methods: This single-center, prospective study included 78 patients who had a diagnosis of HFpEF according to 2016 ESC HF guidelines. 99mTc-PYP cardiac scintigraphy was performed in 43 patients who have ≥2 red flags for TTR-CA including left ventricular hypertrophy (LVH) (wall thickness ≥12 mm), biventricular hypertrophy, sparkling pattern, reduction in longitudinal strain with apical sparing, thickening of the interatrial septum (>6mm), low-voltage, pseudo infarct pattern or atrioventricular block on ECG. In the absence of monoclonal protein in the serum and urine, Grade 2 to 3 myocardial uptake in semi-quantitative analysis at 3 hours or a H/CL ratio of ≥1.5 in quantitative analysis at 1 hour post injection of 99mTc-PYP is considered positive for TTR-CA. Grade 2–3 uptake with a H/CL ratio ≥1.5 or Grade 0–1 uptake with a H/CL ratio <1.5 were considered as concordant results. Grade 2–3 uptake with a H/CL ratio <1.5 or Grade 0–1 uptake with a H/CL ratio ≥1.5 were considered as discordant results. Results: Mean age of study population was 68.26±9.97 years. 17 (39.5%) of 43 patients who underwent 99mTc-PYP cardiac scintigraphy showed a Grade 2 or 3 cardiac uptake and in these patients with Grade 2–3 uptake, 11 patients (65%) had a H/CL ratio ≥1.5 (concordant results) and 6 patients (35%) had a H/CL ratio <1.5 (discordant results). 26 (60.5%) of 43 patients showed Grade 0–1 cardiac uptake. All patients (100%) with Grade 0–1 uptake had a H/CL ratio <1.5 and therefore, showed concordant results. Overall, 37 (86%) patients had concordant and 6 (14%) patients had discordant results (Table 1). Conclusion: The results of this study showed that although there was a high agreement between semi-quantitative and quantitative analysis of 99mTc-PYP cardiac scintigraphy, 14% of patients have discordant results and need further workup to confirm TTR-CA in patients with HFpEF. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Pfizer independent grant.